The length-weight relationships and condition factor of an endemic Marosatherina ladigesi Ahl, 1936 in Walanae Cenranae River Watershed, South Sulawesi, Indonesia - Nasyrah Adiara Firdhita Alam (EDP Sciences, 2021)
Marosatherina ladigesi is an endemic fish species in South Sulawesi and is famous as ornamental fish. However, the biological information of this species is still restricted. This research direct analyzes the length-weight relationships and condition factors of M. ladigesi. Sampling was held monthly from May 2018 to April 2019 in the Walanae Cenranae River Watershed, South Sulawesi. Fish samples were assembled by seine net. A total of 550 M. ladigesi were collected consisted of 227 fish in Camba River, 88 fish in Sanrego River, and 235 fish in Batu Puteh River. The length-weight relationship of male and female fish was W = 0,0002L2,74 and W = 0,00004L3,23 in Camba River, W = 0,0001L2,78 and W = 0,0001L2,92 in Sanrego River, W = 0,0001L2,88 and W = 0,00006L3,12 in Batu Puteh River, respectively. In Camba and Batu Puteh Rivers, the growth pattern of male and female fish were negative allometric and positive allometric, respectively. Conversely, the growth patterns of male and female fish in the Sanrego River were isometric. The condition factor fish in Sanrego River was lower than Camba and Batu Puteh River. These findings are valuable data for establishing a monitoring and conservation of this endemic species in its habitat.